Mucosal HSV-2 Specific CD8+ T-Cells Represent Containment of Prior Viral Shedding Rather than a Correlate of Future Protection - Schiffer, Joshua T. (Frontiers in Immunology, 2013)
It is largely unknown why certain infected hosts shed Herpes Simplex Virus-2 (HSV-2) more frequently and have more severe disease manifestations than others. One idea is that different density or functional capacity of tissue resident effector memory CD8+ T-cells between infected persons may explain phenotypic variability. To generate hypotheses for contrasting shedding patterns in different infected hosts, a spatial mathematical model was employed to evaluate the effects of variability in tissue resident effector memory CD8+ T-cell response, and HSV-2 replication and spread, on viral shedding rate. Model simulations suggest that high levels of CD8+ T-cells in the mucosa do not necessarily indicate a protective phenotype but rather an effective response to recent shedding. Moreover, higher CD8+ T-cell expansion rate and lower viral replication rate, which correlate with better short-term control, may have only a minor impact on long term shedding rates. Breakthrough shedding occurs under all sets of model parameter assumptions, because CD8+ T-cell levels only surpass a protective threshold in a minority of genital tract mucosal micro-regions. If CD8+ T-cell levels are artificially increased using an immunotherapeutic approach, better control of shedding is predicted to occur for at least a year. These results highlight the complex co-dependent relationship between HSV-2 and tissue resident CD8+ lymphocytes during the course of natural infection.